The Role of Spirituality and Biopsychosocial Factors in Predicting Resilience of Pregnant Women - Alrida, Nour A. (Pastoral psychology, 2025)
Pregnancy presents significant physical, emotional, and social challenges, and resilience plays a crucial role in helping women adapt to these demands and maintain better mental health and well-being. This study examines resilience predictors within the biopsychosocial framework, with particular emphasis on the role of spirituality. The study employed a descriptive cross-sectional design to recruit 150 pregnant women from universities and governmental hospitals in Jordan. The participants were aged 18-35 and in their second or third trimester of a low-risk pregnancy. The participants were asked to fill out three surveys: (1) a self-report questionnaire covering sociodemographic factors and perceived social support, (2) the Spiritual Well-Being Scale (SWBS), and (3) the Connor-Davidson Resilience Scale (CD-RISC-25). The majority of the participants were multiparous (69.3%) and unemployed (76.7%) and had a high level of perceived social support (50%). Spiritual well-being was generally moderate (51.3%), as were resilience scores (38%). Hierarchical regression analysis revealed that demographic factors, social support, and spirituality were significant predictors of resilience (p < 0.05). Spearman’s correlation analysis revealed that social support and spirituality were positively associated with resilience among pregnant women (p ≤ 0.05). At the same time, no significant relationships were found with demographic factors, including age, education, parity, employment, or pregnancy trimester (p > 0.05). The present study identifies spirituality and social support as key factors in building resilience among pregnant women. Despite several limitations, including self-reporting bias and convenience sampling, the robust sample size strengthens the findings. The study further proposes practical interventions, such as faith-based counseling and community programs, to foster resilience during pregnancy. These interventions, if implemented effectively, could significantly improve the mental health and well-being of pregnant women, offering hope for better outcomes in maternal health and psychology.